(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Interpretation of formation mechanism and morphology of quartz geodes within Slunfeh Formation deposits using XRD, SEM, EDX, and PLM techniques was done. The XRD results confirmed that mineral composition of the geodes is quartz. SEM photographs showed the existence of embedded Ingredients within the crystalline texture of quartz in form of solid aggregates. EDX analyses revealed that the inclusions belong mainly to calcite mineral. The study of thin sections by PLM showed variation of quartz crystal forms within one geode. The study interpreted that the cauliflower curly outer morphology of geodes has formed as a result of internal inflammation of silica gel followed by reformation of amorphous silica into crystalline quartz. The central cavity of the geode was formed later by recrystallization and dehydration, plus dissolving of embedded non silicate minerals. This study confirmed the non occurrence of silicification of sediment by replacement.